2023
DOI: 10.1002/cey2.310
|View full text |Cite
|
Sign up to set email alerts
|

The decisive role of adsorbed OH* in low‐potential CO electro‐oxidation on single‐atom catalytic sites

Abstract: CO impurity‐induced catalyst deactivation has long been one of the biggest challenges in proton‐exchange membrane fuel cells, with the poisoning phenomenon mainly attributed to the overly strong adsorption on the catalytic site. Here, we present a mechanistic study that overturns this understanding by using Rh‐based single‐atom catalysis centers as model catalysts. We precisely modulated the chelation structure of the Rh catalyst by coordinating Rh with C or N atoms, and probed the reaction mechanism by surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…S13a and S14, when immersed to N 2 -saturated HClO 4 electrolyte, a noticeable peak at ca. 1080 cm −1 arises in the Raman spectra of CoIn-N-C, which corresponds to the metal-OH, as reported in previous literatures 38,39 . Due to the fact that similar peak can only be found in In-N-C, it is inferred that it is In atoms that adsorb OH in the electrolyte, which agrees well with the strong adsorption of OH on In atoms revealed by our calculation results.…”
Section: Resultssupporting
confidence: 79%
“…S13a and S14, when immersed to N 2 -saturated HClO 4 electrolyte, a noticeable peak at ca. 1080 cm −1 arises in the Raman spectra of CoIn-N-C, which corresponds to the metal-OH, as reported in previous literatures 38,39 . Due to the fact that similar peak can only be found in In-N-C, it is inferred that it is In atoms that adsorb OH in the electrolyte, which agrees well with the strong adsorption of OH on In atoms revealed by our calculation results.…”
Section: Resultssupporting
confidence: 79%
“…The chemical activation of water constitutes the key step in the HAT process. , At the catalyst interface, the aggregation of water molecules forms a natural hydrogen-bond (H-bond) network. Previous studies have identified two critical roles of the H-bond network in water chemistry: lowering the energy barrier in water splitting and facilitating rapid proton transfer governed by the Grotthuss mechanism. These two processes occur continuously .…”
Section: Introductionmentioning
confidence: 99%
“…Converting CO 2 into value-added chemicals or fuels is an appealing method for reducing CO 2 emissions and thereby achieving carbon neutrality. Nevertheless, the inertness and thermodynamic stability of CO 2 severely constrain its conversion efficiency. Electroreduction CO 2 (CO 2 RR) has attracted substantial attention from researchers due to its high conversion efficiency, mild reaction conditions, and elevated energy efficiency. The specific products formed depend on the number of protons, electrons, and reduction pathways involved, as the CO 2 RR is a multiproton-coupled and multielectron-transfer processes. , By altering the catalytic conditions or reduction pathways, different surface-bound species can generate corresponding reaction intermediates, leading to the formation of different carbon-containing products such as carbon monoxide (CO), formic acid (HCOOH), methane (CH 4 ), and so on. HCOOH, revered as a high-value CO 2 electroreduction product, is an important raw material in the pharmaceutical and chemical industries, making it one of the most economically viable products in the CO 2 RR process. In the electrochemical reaction mechanism, HCOOH requires minimal electron transfer during the electroreduction process, which not only simplifies the reduction of CO 2 to HCOOH but also allows for its subsequent conversion into other raw materials such as hydrogen (H 2 ), CO, and methanol (CH 3 OH) through simple catalytic reactions to meet various industrial production needs. Therefore, the rational design of catalysts and reduction pathways is crucial to the selectivity and yield of the products.…”
Section: Introductionmentioning
confidence: 99%